2009
DOI: 10.1186/1478-811x-7-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of subpopulations in mesenchymal stem cell-like cultures from human umbilical cord

Abstract: Background: A variety of cell types can be identified in the adherent fraction of bone marrow mononuclear cells including more primitive and embryonic-like stem cells, mesenchymal stem cells (MSC), lineage-committed progenitors as well as mature cells such as osteoblasts and fibroblasts. Different methods are described for the isolation of single bone marrow stem cell subpopulations -beginning from ordinary size sieving, long term cultivation under specific conditions to FACSbased approaches. Besides bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 31 publications
9
100
1
3
Order By: Relevance
“…On the contrary, the classical expansion protocols for BM-MSCs, accepted for clinical use by the regulatory agencies [4], still employ FBS with FGF-2 as the medium additional supplement, which provides excellent results [37,38]. However, with regard to the present study, it should be noted that no major changes were observed in the phenotype characteristics and properties of BM-MSCs expanded in the presence of PL or FBS [34,36,39].…”
Section: Discussionmentioning
confidence: 59%
“…On the contrary, the classical expansion protocols for BM-MSCs, accepted for clinical use by the regulatory agencies [4], still employ FBS with FGF-2 as the medium additional supplement, which provides excellent results [37,38]. However, with regard to the present study, it should be noted that no major changes were observed in the phenotype characteristics and properties of BM-MSCs expanded in the presence of PL or FBS [34,36,39].…”
Section: Discussionmentioning
confidence: 59%
“…51,52 This condition led them to suffer from limited nutrient and oxygen sources. 53,54 Different functional characteristics have been confirmed for hypoxia-induced MSCs from different sources. MSCs have some immunomodulatory effects, 55 especially autocrine or paracrine diverse activity of cytokines, and growth factors of bone marrow-derived MSCs can be modulated in hypoxic conditions.…”
Section: 49mentioning
confidence: 92%
“…In addition, the use of different media and culture conditions may also have an effect on the heterogeneity of UC-MSC population isolated in different laboratories; contributing to the selection and expansion of specific cell populations, which may have not the same behavior under specific culture conditions. In this context, a strategy based on counterflow centrifugal elutriation was used to identify different subpopulations in cultured UC-MSC [17] . The authors revealed that UC-MSC cultures were composed of different sized populations.…”
Section: Discussionmentioning
confidence: 99%